Minimizing Zapping Delay Using Adaptive Channel Switching with Personalized Electronic Program Guide - Timothy T. Adeliyi; Oludayo O. Olugbara; Steven Parbanath (International Journal of Digital Multimedia Broadcasting)
The pervasive acceptability of a revolution from monodirectional push-based media broadcasting to a bidirectional interactive pull-based internet protocol television (IPTV) has spotted significant development in recent years. The pervasive acceptability is because of the mammoth number of exhilarating television (TV) channels that IPTV offers. However, the channel switching feature of a TV system requires additional development despite the increased implementation of IPTV systems worldwide. Subscribers of IPTV services must be able to swiftly explore live TV stations and video contents of interest seamlessly, but zapping delay is a deterrent that occurs during a channel change that causes a significant glitch in IPTV systems. Many of the literature approaches such as channel prediction based on behavior analysis have shown flaws in resolving zapping delay. The approach of this study uses adaptive channel switching with a personalized electronic program guide to resolving zapping delay. The resolution saves the subscribers the time of channel navigation by eliminating the need to search for channels they want to view.